Psychosocial consequences and early life factors impact on the occurrence of childhood sexual assault among secondary school students in Southern Ethiopia: unmatched case-control study - Dinagde, Dagne Deresa; Wada, Habtamu Wana; Negesa, Shambel; Degefa, Bekam Dibaba; Kitil, Gemeda Wakgari; Feyisa, Gizu Tola (Frontiers in Reproductive Health, 2025)
BackgroundChild sexual assault is a violation of fundamental human rights that leads to various negative consequences, including psychological and physical problems. While it is the least reported and addressed form of violence against schoolgirls in Ethiopia, it is a public health issue that affects millions of people globally each year. Thus, this study aims to provide information on the early life factors impact on the occurrence of childhood sexual assault among secondary school students.MethodsAn institution unmatched case-control study was conducted in Arba Minch Zuria district among high school female students attending regular education from March 20, 2023 to May 20, 2023. The data were collected using structured, pretested self-administered questionnaire in all school in Arba Minch Zuria Woreda. Reports of schoolgirls being sexually assaulted were first obtained from the district police office. According to these reports, there were seventy-five (75) cases where the girls were attending or had attended the mentioned high school. In addition, female control students were randomly selected from non-case students. Odds ratio with 95% CI was used as a measure of association, and variables with a p-value of ≤0.05 were considered to be statistically significant.ResultsMultivariate logistic regression analysis was used to identify significant factors. Accordingly factors such as had consumed alcohol (AOR = 4.0, 95CI: 1.68–9.70), living with non-biological parents (AOR = 7.49, 95CI: 2.72–13.65) and living alone (AOR = 4.6, 95CI: 1.49–14.41), being street food vendors (AOR = 4.5, 95CI: 1.48–13.70) and visiting library at improper time (AOR = 5.0, 95CI: 1.87–13.47) were significantly associated with childhood sexual assault.ConclusionHad consumed alcohol, living with non-biological parents and alone, being street food vendors and improper library time were identified as significant determinants of child sexual assault (CSA) among students included in this study. Thus, high schools and families with children should collaborate to develop a plan to reduce sexual abuse that violates children rights. Families should oversee their children to help prevent substance use during their school years. Additionally, parents should remain close to their children, as distancing can lead to exposure to risky relationships.